Epicurus' human beings - beyond person and self - Hirschi, SJ (2020)
Epicurus’ philosophical project is predicated on its eudaimonistic efficacy. His letters and maxims are not only describing a way of life, they actually instantiate his practice of care and reform. To memorise and understand them is meant to actually improve on one’s capacity to reach and maintain a state of ataraxia. They are written and designed to have an impact. Thus, to read Epicurus solely as a theoretician is to turn a blind eye to his agenda. This thesis advocates a stronger reading that takes Epicurus’ intentions at face value. It brings the doctrine closer to its application, through an examination of the readers and intended practitioners of Epicurus’ philosophy: human beings.